Fihrist-i nuskhahā-yi khaṭṭi-yi Fārsī u ʿArabi-yi Kitābkhāna-yi Firdawsī, Kālij Wādhām (Wadham), Dānishgāh-i Āksfūrd (majmūʿa-yi Mīnāsiyān) - Mīr-Anṣārī, ʿAlī (Miras Maktoob, ISBN: 9789004365452., 2019)
In the western world, oriental manuscript collections are now mostly kept at universities, institutes and in national or regional libraries. Yet many of these collections were jumpstarted with the acquisition or donation of some private collection. An example is the oriental collection at Leiden University Library, which started with a legacy of around 60 oriental manuscripts by J.J. Scaliger in 1609. In fact, private collectors have always enriched library collections until this very day. The shelf marks of the oriental manuscripts in almost every major collection in the western world bear testimony to this. Dr Caro Minasian (d. 1973) was an Iranian physician and a passionate collector of oriental manuscripts. In 1968 he sold the greater part of his collection to UCLA (1507 items). In 1972 he bequeathed the remainder (959 titles) to the Ferdowsi library of Wadham College, University of Oxford. This Persian catalogue contains the first detailed description of the entire Minasian collection.